Removal of Chlorinated Chemicals in H2 Feedstock Using Modified Activated Carbon - Prapaporn Luekittisup; Visanu Tanboonchauy; Jitlada Chumee; Somrudee Predapitakkun; Rattanawan W. Kiatkomol; Nurak Grisdanurak (Journal of Chemistry)
Activated carbon (GAC) was impregnated by sodium and used as adsorbent to remove chlorinated hydrocarbon (CHC) gases contaminated in H2 feedstock. The adsorption was carried out in a continuous packed-bed column under the weight hourly space velocity range of 0.8–1.0 hr−1. The adsorption capacity was evaluated via the breakthrough curves. This modified GAC potentially adsorbed HCl and VCM of 0.0681 gHCl/gadsorbent and 0.0026 gVCM/gadsorbent, respectively. It showed higher adsorption capacity than SiO2 and Al2O3 balls for both organic and inorganic CHCs removal. In addition, the kinetic adsorption of chlorinated hydrocarbons on modified GAC fit well with Yoon-Nelson model.